Navigating the Digital Era: A Strategic Analysis of AI Integration in Supply Chain Management and Logistics Performance - Toro, Carlos; Eyong, Danny; Onake, Jean (Journal of Current Research In Multidisciplinary, 2026)
This research explores the transformative impact of Artificial Intelligence (AI) integration on supply chain management and logistics performance within the context of the rapidly evolving digital era. As global markets face increasing volatility and complexity, traditional supply chain models are being challenged to achieve higher levels of responsiveness, transparency, and cost-efficiency. This study adopts a strategic analytical framework to evaluate how AI-driven technologies, including machine learning, predictive analytics, and autonomous systems, function as critical enablers of operational excellence. Through a comprehensive review of current industrial applications and a rigorous analysis of performance metrics, the research identifies a significant correlation between high levels of AI maturity and superior logistics outcomes. The findings suggest that AI not only optimizes routine logistical tasks but also facilitates strategic resilience by enabling proactive risk management and real-time demand forecasting. The study concludes that successful AI integration requires a holistic alignment of technological infrastructure, organizational culture, and cross-functional collaboration. Ultimately, this research provides a strategic roadmap for firms seeking to leverage digital intelligence as a sustainable competitive advantage in the global marketplace.